MEMBANGUN KESADARAN BERPERILAKU SISWA MADRASAH DENGAN PENGUATAN NILAI-NILAI SPIRITUAL - Sulthon, Sulthon (EDUKASIA, 2016)
BUILDING BEHAVIOR AWARENESS OF MADRASA STUDENTS BY STRENGTHENING THE SPIRITUAL VALUES. The age of the students at the madrasa level is in the education age phase where students still have the nature of dependency on the authority of adults in the process of its development. Students as human are essentially have a good nature and always want to do good. However, sometimes they face a variety of challenges and barriers that affect them in behave. Strengthening spiritual values become important in the effort to protect the students’ character towards the formation of positive character. The purpose of this study besides to knowing how to build awareness of the Madrasa Ibtidaiyah students behaved through the inaugural spiritual, as well as to find out the steps in building awareness of the students to behave. Methods in this study focused more on the study of library research where researchers browse some literatures that discuss the consciousness in behave and spiritualism in building awareness of student behavior through spiritualism reinforcement of students in Madrasa Ibtidaiyah. The results of the study leads to a discussion of how student behavior much influenced by the state of one's soul and spirituality.